2011
DOI: 10.1016/j.bpj.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Near-Critical Fluctuations and Cytoskeleton-Assisted Phase Separation Lead to Subdiffusion in Cell Membranes

Abstract: We address the relationship between membrane microheterogeneity and anomalous subdiffusion in cell membranes by carrying out Monte Carlo simulations of two-component lipid membranes. We find that near-critical fluctuations in the membrane lead to transient subdiffusion, while membrane-cytoskeleton interaction strongly affects phase separation, enhances subdiffusion, and eventually leads to hop diffusion of lipids. Thus, we present a minimum realistic model for membrane rafts showing the features of both micros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
102
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 63 publications
15
102
1
Order By: Relevance
“…Moreover, increase of cholesterol submicrometric domains upon acute uncoupling of membrane:spectrin anchorage at 4.1R complexes indicates restriction by protein:based fences [54,55]. These three lines of evidence suggest that cholesterol submicrometric domains are restricted by membrane:spectrin anchorage, in perfect agreement with the picket-fence network which allows confined diffusion of lipids and proteins in mesoscale domains [54,56] while preventing macroscopic domain formation [57,58].…”
Section: Biogenesis Of Cholesterol Submicrometric Domains: Restrictiosupporting
confidence: 52%
“…Moreover, increase of cholesterol submicrometric domains upon acute uncoupling of membrane:spectrin anchorage at 4.1R complexes indicates restriction by protein:based fences [54,55]. These three lines of evidence suggest that cholesterol submicrometric domains are restricted by membrane:spectrin anchorage, in perfect agreement with the picket-fence network which allows confined diffusion of lipids and proteins in mesoscale domains [54,56] while preventing macroscopic domain formation [57,58].…”
Section: Biogenesis Of Cholesterol Submicrometric Domains: Restrictiosupporting
confidence: 52%
“…Formation of Pore-Suspending Membranes Composed of DOPC/Sphingomyelin/Cholesterol/Gb 3 We made use of phase-separated pore-spanning membranes, and we show-as a proof-of-principle-that these bilayers are suitable mimics of the eukaryotic plasma membrane including the underlying cytoskeleton. Pore-spanning membranes were achieved by spreading GUVs on micrometer-sized functionalized highly ordered pore-arrays with pore diameters of 0.8, 1.2 and 2 mm (see Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…Monte Carlo simulations provide evidence that the membrane-cytoskeleton interaction strongly affects phase separation in lipid bilayers. [3] It was demonstrated that the cytoskeleton inhibits large-scale phase separation, which might explain why micrometer-scaled domains are observed in giant unilamellar vesicle membranes [4] as a result of a minimization of the line tension occurring at the border of different lipid compositions [5] but not in plasma membranes of living cells. [6] Thus, to create a more realistic model of the plasma membrane, not only the membrane composition has to be properly adjusted but also the underlying cytoskeleton has to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of immobile clustered obstacles on diffusion have been investigated in several theoretical studies (44,57,58,71). It was shown by Saxton (43) that a percolation threshold, c p , exists when the occupied area fraction of obstacles, c, exceeds 0.332.…”
Section: Existence Of Racks Of Rhodopsin Dimersmentioning
confidence: 99%